2021
DOI: 10.1155/2021/3154501
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Tongyang Huoxue Decoction (TYHX) Ameliorating Hypoxia/Reoxygenation‐Induced Disequilibrium of Calcium Homeostasis and Redox Imbalance via Regulating Mitochondrial Quality Control in Sinoatrial Node Cells

Abstract: Sick sinus syndrome (SSS) is a disease with bradycardia or arrhythmia. The pathological mechanism of SSS is mainly due to the abnormal conduction function of the sinoatrial node (SAN) caused by interstitial lesions or fibrosis of the SAN or surrounding tissues, SAN pacing dysfunction, and SAN impulse conduction accompanied by SAN fibrosis. Tongyang Huoxue Decoction (TYHX) is widely used in SSS treatment and amelioration of SAN fibrosis. It has a variety of active ingredients to regulate the redox balance and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…TCM has a long history. The overall philosophy of TCM is closely related to the core ideas of network pharmacology and network biology, which can systematically overcome complex diseases such as CVD [ 42 , 43 ]. Thus, it is of great significance to study the treatment of MI with TCM from the perspective of gut microbiota and network pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…TCM has a long history. The overall philosophy of TCM is closely related to the core ideas of network pharmacology and network biology, which can systematically overcome complex diseases such as CVD [ 42 , 43 ]. Thus, it is of great significance to study the treatment of MI with TCM from the perspective of gut microbiota and network pharmacology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the active ingredients of traditional Chinese medicine, the compound preparation of traditional Chinese medicine can also have a certain regulatory effect on the interaction mechanism of mitochondrial dynamics and mitophagy. Tongyang Huoxue Recipe, a traditional Chinese medicine compound, can protect sinoatrial node cells under stress through PINK/parkin-mediated mitophagy, and can also inhibit DRP1-mediated mitochondrial fusion/fission dysfunction, increase mitochondrial membrane potential, maintain calcium homeostasis, and inhibits oxidative stress damage (194). Zishen Huoxue Decoction is an effective compound for the treatment of patients with coronary heart disease.…”
Section: Mitochondrial Targeted Natural Medicines Therapymentioning
confidence: 99%
“…The degradation of the fusion protein Mfn1/2 up to a certain level can maintain the mitochondria in a fission state, which may be necessary for mitophagy. Increased levels of mitophagy protect cardiomyocytes under certain stress conditions [ 106 ]. For example, Parkin-mediated mitophagy protects against high glucose- and palmitate-induced cardiomyocyte injury.…”
Section: Mitophagymentioning
confidence: 99%
“…Natural medicines and their active compounds have multitarget comprehensive curative effects [ 136 , 137 ] ( Figure 7 ). Many natural medicines and their active compounds, such as aconite, bupleurum, and astragalus, protect cardiomyocytes, enhance myocardial contractility, dilate blood vessels, induce diuresis, and reduce ventricular remodeling; these are widely used in the treatment of heart failure [ 12 , 106 ]. Studies have also found that natural active compounds extracted from traditional natural medicinal plants have anti-inflammatory, antioxidative, and antiapoptotic actions, while improving fatty acid oxidation and autophagic effects [ 130 , 136 ].…”
Section: Natural Medicinal Plants and Active Ingredients In The Regul...mentioning
confidence: 99%